Diaspora Politik Keluarga Organisasi Nahdlatul Wathan pada Pemilu Legislatif 2014 di Lombok, Nusa Tenggara Barat - FAHRURROZI FAHRURROZI (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2017)
This article confirms that the decision of Nahdlatul Wathan organization not to engage in the field of practical politics cannot be separated from the fact that a number of the organization’s members do the opposite. Hence, such contradic-tion may lead to a conflict of interest between the organization’s missions, which are to solely focus on three main domains of activities: education, social transfor-mation, and dakwah islamiyah, with a number of practically engaging members in politics who may take advantage of their Nahdlatul Wathan organizational posi-tion to raise voters. Apart from their mission statement, Nahdlatul Wathan al-ways takes a strategic position in the political culture of West Nusa Tenggara. This can be observed from three aspects: (1) the supported political party, (2) the owned social capital and (3) the massive organization’s role. Based on these three aspects, the Nahdlatul Wathan and a number of its members always participate in assuming legislative and executive powers.